The effects of age-bias on neural correlates of successful and unsuccessful response inhibition - Claire Hanley (Behavioural Brain Research, 2022)
Response inhibition is important for adherence to social norms, especially when norms conflict with biases based on one’s social identity. While previous studies have shown that in-group bias generally modulates neural activity related to stimulus appraisal, it is unclear whether and how an in-group bias based on age affects neural information processing during response inhibition. To assess this potential influence, young adults completed a Go/NoGo task incorporating younger face (in-group) and older face (out-group) stimuli while undergoing functional magnetic resonance imaging (fMRI). Our results replicated previous findings by demonstrating higher accuracy in successful Go compared to NoGo trials, as well as the engagement of nodes of the response inhibition network during successful response inhibition, and brain regions comprising the salience network during unsuccessful response inhibition. Importantly, despite a lack of behavioural differences, our results showed that younger and older face stimuli modulated activity in the response inhibition and salience networks during successful and unsuccessful inhibition, respectively. Interestingly, these effects were not uniform across networks. During successful response inhibition, in-group stimuli increased activity in medial prefrontal cortex and temporo-parietal junction, whereas out-group stimuli more strongly engaged pre-supplemental motor area. During unsuccessful response inhibition, in-group stimuli increased activity in posterior insula, whereas out-group stimuli more strongly engaged angular gyrus and intraparietal sulcus. Consequently, the results infer the presence of an age-bias effect in the context of inhibitory control, which has substantial implications for future experimental design and may also provide the means of investigating the neural correlates of implicit beliefs that contribute to ageism.